Sistem Pendidikan Pondok Pesantren di Indonesia (Suatu Kajian Sistem Kurikulum di Pondok Pesantren Lirboyo) - Kholid Junaidi (Postgraduate Program Magister Pendidikan Agama Islam, 2017)
The background of this writing is still an assumption of some people consider boarding school is an institution of education that is less orderly, rule out the affairs of the world even assuming the boarding school is a hotbed of terrorists. Such views should be thrown away because they in fact boarding an Islamic educational institutions that their major contribution to Islamic civilization in Indonesia and Indonesian human superbly managed to form a virtuous, noble, understand and live the teachings of Islam. This success is due to the boarding school has successfully established a system of education that is contextual to the needs of the people of Indonesia. The formulation in this paper are: (1) How is the system of teaching in a boarding school? (2). How the educational curriculum at boarding school? The results showed that (1) Systems of teaching at the boarding school system is divided into two classical learning and the learning system non klaskal. Learning system adopted from the classical modern education system that is on the students grouped by grade level appropriate ability level, Level Madrasah Ibtida'iyah, Tsanawiyah level (Mts), the level of Aliyah (MA), levels I'dadiyyah (SP). While the non-classical learning system directly supervised by clerics with sorogan and bandongan system. (2) The curriculum of education in boarding broadly divided into 7 groups of subjects of fiqh, hadith, quran, monotheism, Arabic literature, Sufism, commentary, on each of these subjects boarding school has determined the book used by grade level or the ability of students.